A 2D Tide-Averaged Model for the Long-Term Evolution of an Idealized Tidal Basin-Inlet-Delta System - Giulio Mariotti; Shamim Musrhid (Journal of Marine Science and Engineering, 2018)
We present a model for the morphodynamics of tidal basin-inlet-delta systems at the centennial time scales. Tidal flow is calculated through a friction dominated model, with a semi-empirical correction to account for the advection of momentum. Transport of non-cohesive sediment (sand) is simulated through tidal dispersion, i.e., without explicitly resolving sediment advection. Sediment is also transported downslope through a bed elevation diffusion process. The model is compared to a high-resolution tide-resolving model (Delft3D) with good agreement for different hydrodynamic and sedimentary settings. The model has low sensitivity with respect to temporal and spatial discretization. For the same spatial resolution, the model is about five orders of magnitude faster than tide-resolving models (e.g., Delft3D), and about three orders of magnitude faster than tide-resolving models that use a morphological acceleration factor. This numerical efficiency makes the model suitable to assess long-term changes of large coastal areas. The model’s simplicity makes it suitable for coupling with other physical, ecological, and socio-economic dynamics.